2001
DOI: 10.1007/s000110050732
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of the neutrophil-derived protein YKL-40 during storage of various blood components

Abstract: YKL-40 appears to accumulate extracellularly in a time-dependent manner in standard erythrocyte components. Prestorage leukocyte depletion by filtration of whole blood may be an effective procedure to prevent extracellular YKL-40 accumulation during storage of erythrocyte components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
2
2
0
Order By: Relevance
“…Similar results have been shown with histamine infusion and tumor growth [38]. Therefore, in addition to other tumor growth modulating bioactive substances present in blood components for transfusion, such as in particular PAI-1 [30,31], TIMP-1 [39,40], and YKL-40 [41,42], VEGF, and histamine may potentially participate in a concerted action, which may support the tumor growth stimulatory role of various blood transfusion components [43,44].…”
Section: Discussionsupporting
confidence: 73%
“…Similar results have been shown with histamine infusion and tumor growth [38]. Therefore, in addition to other tumor growth modulating bioactive substances present in blood components for transfusion, such as in particular PAI-1 [30,31], TIMP-1 [39,40], and YKL-40 [41,42], VEGF, and histamine may potentially participate in a concerted action, which may support the tumor growth stimulatory role of various blood transfusion components [43,44].…”
Section: Discussionsupporting
confidence: 73%
“…In particular, in contrast with previous evidence from CSF [ 7 ], the plasmatic levels of CHI3L1 did not correlate with the score of the executive and visuo–spatial neuropsychological tests. The only correlation that was observed was with haemoglobin and RBC; this is consistent with previous evidence, since CHI3L1 seems to be more concentrated in RBCs [ 22 ].…”
Section: Discussionsupporting
confidence: 91%
“…It is suggested that neutrophil-released YKL-40 acts as an autoantigen in rheumatoid arthritis (RA). Moreover, release of YKL-40 from specific neutrophil granules was suggested to lead to the post-transfusional complications and can be prevented by the pre-storage leukocyte depletion by filtration of whole blood (Cintin et al 2001). …”
Section: Intracellular Sorting and Modes Of Secretionmentioning
confidence: 99%